Population Density of Soil Mesofauna in Secondary Forest, Palm Oil Agroforestry using Agarwood Gharu and Community Rubber Gardens in Kampar District - Firdaus Amir; Hapsoh Hapsoh; Delita Zul (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2023)
Soil mesofauna plays a role in fertilizing the soil and plants. Soil mesofauna is one of the soil organisms that can provide information about soil quality and fertility. This study aims to analyze the population density of soil mesofauna in secondary forests, oil palm agroforestry with agarwood and community rubber plantations in Kampar Regency. Soil sampling using purposive sampling method and soil mesofauna sorting using a barless tullgreen tool. The results showed that the total population density of soil mesofauna in oil palm agroforestry with agarwood was 102.67 indv/m2, rubber plantations were 96.00 indv/m2, and the secondary forest was 85.33 indv/m2. The soil mesofauna family that was primarily obtained in the secondary forest was the Hahniidae family (21 individuals), the oil palm agroforestry with agarwood was the Formicidae family (35 individuals) and in the rubber plantations, the Formicidae family (20 individuals). Information on the population density of soil mesofauna in secondary forests, oil palm agroforestry with agarwood and rubber plantations in Kampar Regency becomes data for better environmental management.